Uso de marcadores bioquímicos no diabetes tipo 2 como parâmetro de monitorização no acompanhamento farmacoterapêutico de pacientes : uma abordagem em atenção farmacêutica - Nogueira, Luciana Macatrão (2008)
Individualized Pharmaceutical Care (PC) practice in Diabetes, monitoring biochemical parameters, is a very important activity once that it provides better clinical and it helps to improve the diabetic patients’ health quality. Objective: The aim of this work was to present and to analyze, through a Pharmaceutical Care (PC) plan for patients with Diabetes Mellitus type 2, the drug related problems (DRP) and the implantation of endhotelial dysfunction biochemical markers as parameters of monitor the pharmacotherapeutic follow-up. Methods: The study was carried out with a group of diabetic patients attended at Centro de Pesquisas em Diabetes e Doenças Endocrinometabólicas during the period from June-2006 to June-2007. The research was developed with 101 patients and counted on the effective participation of 58 patients until its conclusion. The patients had participated of 7 visits to the center, where they had been interviewed, they had carried out laboratorial determinations and they had received the orientation from the developed plan for the pharmaceutical attention service. Results: It was observed the feminine gender predominance (58.4%) when compared to the masculine (41.58%). Arterial hypertension was associated in 54.4% of diabetic patients. A significant percentage of the patients (64%) was sedentary and presented diagnostic of diabetes since less than 10 years (84.2%). The general state of the patients’ condition while analyzing parameters GJ, CT, LDL-C and HbA1c had improved after 6 months of PC. 96.70% of the patients had presented dyslipidemia in the beginning of PC and this value had decreased to 64.29% 3 months after, increasing again to 81,04% after 6 months. The percentage of the patients with dyslipidemia classified for low HDL in the beginning of PC was 96,70%, and this number had decreased to 92.6% after 3 months of PC plan. Conclusion: PC practice was firmed as an efficient instrument in patient’s adhesion to the therapeutic plan, as well as in the improvement of the diabetic individuals life quality, also helping the prevention of some complications like those ones related to cardiovascular conditions.